EFEKTIVITAS PUPUK BIO-SLURRY DAN Trichoderma harzianum TERHADAP PENINGKATAN PRODUKSI TANAMAN MENTIMUN (Cucumis sativus L.) - Rahmawati, Sri; Aminah, Aminah; Abdullah, Abdullah (Percetakan Umi Toaha Makassar, 2025)
This study aimed to: (1) analyze the effect of the best interaction between organic fertilizer Bio-Slurry and Trichoderma harzianum on increasing cucumber production; (2) analyze the optimum dose of Bio-Slurry organic fertilizer for improving cucumber production; and (3) analyze the optimum dose of Trichoderma harzianum that provides the best effect on cucumber production. The research was conducted at P4S Wanua Lampoko, located in Cinennung Village, Cina Subdistrict, Bone Regency, South Sulawesi Province, from May to July 2025. This study was an experimental research with a quantitative approach using a Randomized Block Design (RBD) and a factorial treatment design. The factorial treatment design was chosen to analyze the interaction between the two treatment factors applied, namely Bio-Slurry fertilizer and Trichoderma harzianum. The results showed that there was a significant interaction between Bio-Slurry fertilization and Trichoderma harzianum on the growth and production of cucumber plants, where their combination provided better results compared to single treatments. Bio-Slurry fertilization was proven to affect the growth and production of cucumber plants, with the optimum dose at 100 ml/l, which produced higher yield, particularly on the parameter of fruit weight per plot. Meanwhile, the application of Trichoderma harzianum also showed a significant effect, with the optimum dose ranging between 200–300 g/plant. The best combination was obtained with the treatment of Bio-Slurry 100 ml/l and Trichoderma harzianum 300 g (B4T3), which produced the highest yield of 5.00 kg per plot; thus it can be recommended as an effective organic fertilization strategy to improve cucumber yield.